Outcome on Surgical Site Infections for the Closure of Abdominal Incisions in General Surgery - Shiraz Shaikh, Zameer Hussain Laghari, Qamber Ali Laghari, Aisha Memon, Sahrish, Arif Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of surgical site infections according to the closure of abdominal incisions (skin staplers versus suture stitches) in General Surgery at Liaquat University of Medical and Health Sciences (LUMHS). Material and Method: This cross-section comparative study was conducted at the Department of General Surgery at LUMHS. The study was conducted for one year from January 2021 to December 2021. All the patients aged more than 12 years, both genders and who had undergone abdominal surgeries were included. Patients were divided into two groups group A and group B as per closure of the abdominal incisions. Patients in group A underwent staplers wound closure and patients in group B underwent wound closure by suture stitches. Patients were assessed for postoperative surgical site infection during hospital stay. All the data were collected via self-made study proforma. SPSS version 26 was used for the purpose of data analysis. Stratification with respect to the effect modifiers was done and a p-value < 0.05 was taken as significant. Results: In this study, a total of 41 cases were comparatively studied regarding surgical site infections as to the type of wound closure. The average age of the stapler’s patients’ group was 36.70+6.22 years and the average age of the suture patients’ group was 42.47+5.09 years. Males were most common in both groups without a significant difference (p-929), while average duration of closure was significantly lower in stapler group as compared to suture group (p-0.001). Of all, 12 cases had wound infection, particularly as 4 cases had infection grade I, 5 cases had grade II infection and 2 cases had grade III infection. Although frequency of surgical site infection was statistically insignificant (p-0.223). Conclusion: The wound closure skin stapler’s method was observed to be effective in terms of short duration, while the frequency of surgical site infection was higher in stapler closure but statistically insignificant as per both techniques.